Apelin - a new protein-regulator in the cardiovascular system - Sergey Nikolaevich Tereshchenko; Valeriy Pavlovich Masenko; Ol'ga Vladimirovna Cherkavskaya; Nadezhda Viktorovna Shashkova; S N Tereschenko; V P Masenko; O V Cherkavskaya; N V Shashkova (Терапевтический архив, 2009)
Apelin is an endogenic ligand of apelin (APJ) receptors widely expressed in human tissues. This protein is a peripheral vasodilator having a powerful positive inotropic action on myocardial contractility. This review describes mechanisms of interaction and apelin role in health and pathology.